Effects of oral gavage with periodontal pathogens and plaque biofilm on gut microbiota ecology and intestinal tissue architecture in mice: a mechanistic study - Lan Huang; Song Ge; Kun Yang; Lian Duan; Li Gao; Yu Zhen Li; Yu Shi Yi (Frontiers in Cellular and Infection Microbiology)
ObjectiveThis study aimed to establish an in vitro model simulating periodontal biofilm architecture with three representative periodontal pathogens and evaluate its systemic impact through oral gavage administration in C57BL/6 mice. The findings provide mechanistic insights into the oral-gut axis dysbiosis, elucidating potential pathways linking periodontal inflammation to gastrointestinal pathophysiology.MethodsFifty 7-week-old male C57BL/6 mice were randomized into five groups(n=10/group): control (H), F. nucleatum (F), P.gingivalis (P), S.sanguinis (S) and biofilm (BF, F.n + P.g + S.s) groups. Mice were gavaged twice weekly for 6 weeks with 1×109 CFU (F, P, BF groups) and 1×108 CFU (S group) of bacterial suspensions or PBS (H group). Post-intervention, fecal and colon tissues were collected for 16S rRNA sequencing, H&E staining, immunohistochemistry (Occludin expression), and qRT-PCR analysis of inflammatory markers(IL18, TNF-α, IL-1β, B220, F4/80, NOS2, ARG1).ResultsA stable in vitro three-species biofilm model was successfully established to mimic the ecology of periodontal plaque. Gavage with F.n, P.g or the biofilm consortium (BF group) induced intestinal barrier disruption and elevated pro-inflammatory cytokines levels. PCR indicated a significant increase in the expression of IL-1β, TNF-α, B220, F4/80, and NOS2 in the P group (P < 0.001), while Arg-1 expression exhibited a significant decrease (P < 0.01). In the BF group, only TNF-α expression demonstrated a significant increase (P < 0.01). The expression of occludin is significantly reduced in the F/P/BF group, with the most pronounced decrease observed in the P group (P < 0.01). Gut microbiota alterations occurred in all groups. At the phylum level, the Firmicutes/Bacteroidetes (F/B) ratio increased in all three groups (F/P/BF group). Proteobacteria abundance rose substantially in the P group, while Desulfovibrio increased and Verrucomicrobia decreased in the F/P/BF and F/S groups, respectively. Genus-level analysis showed reduced Muribaculaceae in the F/P/BF group, alongside elevated pro-inflammatory bacteria (e.g., Enterococcus, Acinetobacter) and diminished beneficial bacteria (e.g., Bifidobacterium, Parabacteroides).ConclusionThese findings demonstrate that periodontal pathogens induce gut barrier compromise through microbiome-driven immunomodulation, with P. gingivalis exhibiting predominant pro-inflammatory effects.